Addressing the Press Websites of Cyclone “Laban” Disaster in Yemen - Bakhash, Abdullah Omar (ALBAHITH ALALAMI, 2025)
This study has sought to explore the Yemeni online news websites’ treatment of the tropical storm “Luban” which hit the coasts of al-Mahra governorate, and other parts of the Yemeni Eastern and Southern governorates in October 2018. The study also examined how the Yemeni news websites covered the disaster on the basis of the problematic situation model. The study’s findings revealed a form of logical balance in distributing the coverage of the disaster in its different phases. The coverage was a bit more focused on the disaster phase than the pre- and post-disaster phases. Additionally, the websites paid more attention to precautionary measures and the disaster’s humanitarian and material losses. The findings reveal that the news website’s coverage of “Luban” was balanced and that they all determined the same disaster’s reasons, and focused on highlighting the consequences of the disaster’s humanitarian and material disaster. The results show homogeneity and balance in regard to suggesting solutions for addressing the disaster and ordering the responsible authorities. Keywords: Electronic press, crisis and disaster communication, Luban storm, Yemen.